ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRATEGI USAHA KECIL DAN MENENGAH DI KABUPATEN SEMARANG - Eka Handriani (Jurnal Ekonomi dan Bisnis, 2009)
The purpose of this research is to proof that internal and external factor, entrepreneur skilland ethos are influence to the strategy which applied in the UKM of Kabupaten Semarangsimultaneously and partially. Micro entrepreneur has great potency in the national and localeconomic according to this free market period. However, it is ethos and competition still inthe low level. The main cause of this problem come up from environmental exertion factor,among them are internal and external factor also the entrepreneur skill. In order to solve thisproblem need an accurate strategy to survive. This research purposed to study the influenceof external and internal environment, entrepreneur skill and ethos on the micro entrepreneurstrategy in Kabupaten Semarang. A causal research has been done on 60 micro entrepreneursthrough four dependent variables and one independent variable using SPSS. The resultshown that internal and external factor, entrepreneur skill and ethos has significant influencedon the strategy that applied by the micro entrepreneur in Kabupaten Semarang partially orsimultaneously.Keyword : Performance, Entrepreneur Skill, Strategy, Invironment Factor.